An increase in racism during the COVID-19 pandemic and the ontology of race - Rošker, Jana S. (Economic and business review, 2021)
The article treats intercultural problems of global-scale crises, focusing upon the pandemic of the viral disease COVID-19. It deals with the question of whether racism is universal or culturally conditioned, and shows that it is an ideological inheritance of the ontological status of the concept of race, which was developed and established in the context of the European ideational tradition. By presenting traditional Chinese models of relational and anti-essentialist concepts of the self, the article aims to point to new possibilities of understanding interpersonal and intercultural interactions that can help us to develop new strategies against the pandemic.
Keywords: China; COVID-19; East Asia; Kitajska; ontologija; ontology of race; racism; rase; rasizem